The diplomatic mission of Stanisław Mateusz Rzewuski to Turkey in 1699 - Gliwa, Andrzej (Balcanica Posnaniensia. Acta et studia, 2003)
The article presents the course and circumstances of Stanisław Mateusz Rzewuski's diplomatic mission, who, as an extraordinary envoy of the Polish-Lithuanian Commonwealth, travelled to Turkey to ratify the Karłowice treaties and normalise relations with the Ottoman Empire. The aim of the research is to reconstruct the course and significance of Rzewuski's mission in the context of late 17th-century diplomacy. The problems encountered by the Polish envoy, both on the political and legal level and in terms of logistics, are highlighted. The source base consists of the envoy's correspondence, Sejm documents and contemporary accounts. The analysis shows that despite numerous obstacles – delays, disputes over the interpretation of the treaty, incidents involving the Tatars, and financial and organisational difficulties – Rzewuski's mission was a success. The Treaty of Karlowitz was formally ratified, and the Polish MP was received with dignity by the Ottoman authorities. The author emphasises that Rzewuski's mission was crucial for stabilising Polish-Turkish relations at the end of the 17th century.